Mechanical stretch decreases FAK phosphorylation and reduces cell migration through loss of JIP3-induced JNK phosphorylation in airway epithelial cells - Desai, Leena P. (American Physiological Society, 2009)
JNK is a nonreceptor kinase involved in the early events that signal cell migration after injury. However, the linkage to early signals required to initiate the migration response to JNK has not been defined in airway epithelial cells, which exist in an environment subjected to cyclic mechanical strain (MS). The present studies demonstrate that the JNK/stress-activated protein kinase-associated protein 1 (JSAP1; also termed JNK-interacting protein 3, JIP3), a scaffold factor for MAPK cascades that links JNK activation to focal adhesion kinase (FAK), are both associated and activated following mechanical injury in 16HBE14o− human airway epithelial cells and that both FAK and JIP3 phosphorylation seen after injury are decreased in cells subjected to cyclic MS. Overexpression of either wild-type (WT)-FAK or WT-JIP3 enhanced phosphorylation and kinase activation of JNK and reduced the inhibitory effect of cyclic MS. These results suggest that cyclic MS impairs signaling of cell migration after injury via a pathway that involves FAK-JIP3-JNK.